Evaluation of Blood Glial Fibrillary Acidic Protein as a Potential Marker in Huntington's Disease - You, Huajing; Wu, Tengteng; Du, Gang; Huang, Yue; Zeng, Yixuan; Lin, Lishan; Chen, Dingbang; Wu, Chao; Li, Xunhua; Burgunder, Jean-marc; Pei, Zhong (Frontiers in Neurology, 2021)
Objective: Huntington’s disease (HD) is an autosomal dominant neurodegenerative disorder. Neurofilament light protein (NfL) is correlated with clinical severity of HD but relative data is lack in Chinese population. Reactive astrocytes are related to HD pathology, which predicts their potential to be a biomarker in HD progression. Our aim was to discuss the role of blood glial fibrillary acidic protein (GFAP) to evaluate clinical severity in HD patients. Methods: Fifty-seven HD mutation carriers and 26 healthy controls were recruited. Demographic data and clinical severity assessed with internationally Unified Huntington’s Disease Rating Scale (UHDRS) were retrospectively analysed. Plasma NfL and GFAP were quantified with an ultra-sensitive single-molecule (Simoa) technology. We explored their consistency and their correlation with clinical severity. Results: Compared with healthy controls, plasma NfL (p<0.0001) and GFAP (p<0.001) were increased in Chinese HD mutation carriers and they were linearly correlated with each other (r=0.612, p<0.001). They were also significantly correlated with disease burden, Total Motor Score (TMS) and Total Functional Capacity (TFC). The scores of stroop word reading, symbol digit modalities tests and short version of the Problem Behavious Assessment for HD (PBAs) were correlated with plasma NfL but not GFAP. Compared with healthy controls, plasma NfL has been increased since stage 1 but plasma GFAP began to increase statistically in stage 2. Conclusions: Plasma GFAP was correlated with plasma NfL, disease burden, TMS and TFC in HD mutation carriers. Plasma GFAP may have a potential to be a sensitive biomarker for evaluating HD progression.